Hybrid wireless mesh protocol - YANG Kai1; MA Jian-feng1 (Tongxin xuebao)
Hybrid wireless mesh protocol（HWMP）, the default routing protocol of IEEE 802.11s, was described.HWMP provided two routing modes:on-demand and proactive.An efficient cooperation method of the two routing modes was proposed.It was implemented and its performance was evaluated.The experimental results show that HWMP has lower average latency and higher data transmission throughput compared with ad-hoc on demand distance vector routing（AODV）.